Site Component—k0 and Its Correlation to VS30 and the Site Fundamental Frequencies for Stations Installed in N. Macedonia - Marina Poposka; Davor Stanko; Dragi Dojchinovski (Geotechnics)
This study focuses on determining the high-frequency decay parameter kappa (k) and its site component (k0) for sixteen accelerometric stations installed in suitable locations in North Macedonia. Kappa characterizes the attenuation of ground motion at high frequencies, describing the decrease in the acceleration amplitude spectrum. It is defined using a regression line in log-linear space, starting from the point where the S-wave amplitude spectrum begins to decay rapidly. The site characteristics of the stations are determined through geophysical and borehole investigations, as well as HVSR mean curves derived from earthquake data. The strong-motion data used in this analysis originate from earthquake events with a moment magnitude greater than 3 (MW > 3), an epicentral distance less than 120 km (Repi < 120 km), and a focal depth lower than 30 km (h < 30 km). The records undergo visual inspection and filtering, with those having a signal-to-noise ratio (SNR) below 3 excluded from further analysis. The study examines the correlation between kappa values and various parameters, including magnitude, epicentral distance, average shear-wave velocity in the top 30 m depth (VS30), and fundamental site frequency (f0). The importance of this study is the application in the future evaluation/update of seismic hazard analysis of the region.